2017
DOI: 10.1155/2017/7371010
|View full text |Cite
|
Sign up to set email alerts
|

Eag1 K+ Channel: Endogenous Regulation and Functions in Nervous System

Abstract: Ether-à-go-go1 (Eag1, Kv10.1, KCNH1) K+ channel is a member of the voltage-gated K+ channel family mainly distributed in the central nervous system and cancer cells. Like other types of voltage-gated K+ channels, the EAG1 channels are regulated by a variety of endogenous signals including reactive oxygen species, rendering the EAG1 to be in the redox-regulated ion channel family. The role of EAG1 channels in tumor development and its therapeutic significance have been well established. Meanwhile, the importanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 113 publications
(193 reference statements)
0
13
0
Order By: Relevance
“…In addition, eag1 channels are affected by other signalling substances such as arachidonic acid, oestrogen or progesterone (Han et al . ). In heteromeric eag channels the slow time course of eag2 activation dominates (Schonherr et al .…”
Section: Introductionmentioning
confidence: 97%
“…In addition, eag1 channels are affected by other signalling substances such as arachidonic acid, oestrogen or progesterone (Han et al . ). In heteromeric eag channels the slow time course of eag2 activation dominates (Schonherr et al .…”
Section: Introductionmentioning
confidence: 97%
“…Voltage gated channels of the EAG family are inhibited by intracellular calcium [58]. One function of Fkpb9 besides acting as a prolyl cis-trans isomerase is mediated through its calcium binding Ef-H domain [59].…”
Section: Discussionmentioning
confidence: 99%
“…The human Ether à go-go channels (hEAG1) are expressed in various types of cancer cells and central nervous system which makes the channel a potential therapeutic target of many cancers and neuronal disorders 10,11,12,13,14 . The electrophysiological study in our lab has confirmed the inhibitory effect of phosphatidylinositol 4, 5-bisphosphate (PIP 2 ) on hEAG1 channel 15 .…”
Section: Introductionmentioning
confidence: 99%